Bared to you - Day, Sylvia (New York : Berkley Books, 2012)
Eva Trammel, plagued by her own insecurities, is drawn into an intense, obssessive relationship with the wealthy and arrogant Gideon Cross.
Includes readers guide.
"A crossfire novel"--Cover.
Keywords: Man-woman relationships -- Fiction; Obsessive-compulsive disorder -- Fiction; Erotic fiction; Love stories